Complication on Teenage Pregnancy and Related Factors - Omo A Madjid; Nanda I S Roesman (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To evaluate related factors, which contribute to complication of teenage pregnancy. Method: A cross-sectional research by consecutive sampling method was held upon teenager who was having her first pregnancy or had just been having her first child. This research took place at dr. Zainoel Abidin Public Hospital, Banda Aceh, in period of June until November 2012. Result: By demographic characteristic, we obtained that the majority of complication of teenage pregnancy occur in the age range of 17-19 years old and most are within Sex maturation Rate grade 5. The most common complications are caesarean section, premature rupture of membranes and cephalo-pelvic disproportion. There is a significant relation between antenatal visit conducted in accordance with WHO criteria and economic level with the incidence of complication. Conclusion: We found significant relation between antenatal visit conducted in accordance with WHO criteria and economic level with the incidence of complication. Keywords: complications, teenage pregnancy.